2012
DOI: 10.1016/j.jpba.2011.12.035
|View full text |Cite
|
Sign up to set email alerts
|

A homogeneous fluorescent sensor for human serum albumin

Abstract: Human serum albumin is the most abundant protein in the body and is an important biomarker used for disease-related diagnosis. Although the traditional enzyme-linked immunosorbent assay (ELISA) approach can precisely measure the concentration of human serum albumin, the multi-step procedure and time-consuming preparations of ELISA limit its diagnostic applications, preventing accurate point-of-care testing, for example. Herein, we report the recent development of an antibody-based albumin sensor that allows fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(43 citation statements)
references
References 25 publications
(33 reference statements)
2
41
0
Order By: Relevance
“…A similar observation also reported that the binding capacity of a cryogel towards template human serum albumin (HSA) present in non‐diluted serum is 390.2 mg/g whereas the binding capacity in binding studies is 25.9 mg/g , and also in our previous work reported, MIP towards HSA showed maximum adsorption capacity in urine (129.5 mg/g) whereas the binding capacity in binding studies is 86.7 mg/g . The UA , creatinine , and HSA in the human urine are found to be as ∼0.63–13.6 mM, ∼2.12–17.1 mM, and ∼0.2–0.39 µM, respectively. However, the adsorption capacity of human serum albumin (IF, 1.05) as well as creatinine (IF, 1.21) and uric acid (IF, 1.15), which are final metabolites in urine, is not very significant compared to ATP adsorption efficiency, suggesting that the interference of other metabolites to these ATP binding sites is nonspecific.…”
Section: Resultssupporting
confidence: 76%
“…A similar observation also reported that the binding capacity of a cryogel towards template human serum albumin (HSA) present in non‐diluted serum is 390.2 mg/g whereas the binding capacity in binding studies is 25.9 mg/g , and also in our previous work reported, MIP towards HSA showed maximum adsorption capacity in urine (129.5 mg/g) whereas the binding capacity in binding studies is 86.7 mg/g . The UA , creatinine , and HSA in the human urine are found to be as ∼0.63–13.6 mM, ∼2.12–17.1 mM, and ∼0.2–0.39 µM, respectively. However, the adsorption capacity of human serum albumin (IF, 1.05) as well as creatinine (IF, 1.21) and uric acid (IF, 1.15), which are final metabolites in urine, is not very significant compared to ATP adsorption efficiency, suggesting that the interference of other metabolites to these ATP binding sites is nonspecific.…”
Section: Resultssupporting
confidence: 76%
“…Similar to HSA, UV visible spectra showed the absorption band at 280 nm for the urine sample. Also, the concentration of protein in urine is calculated to be 3.38 ± 0.0012 mg L −1 which is absent in the synthetic urine sample and is in the range of literature . The binding capacity of MIP toward HSA in real urine (125.3 mg g −1 ) is higher than in the synthetic urine (62.5 mg g −1 ) due to other peptides present in the real urine which indicated that the effect of amounts of the diffused protein template, that was associated with the perturbation of the complex interferences in the urine.…”
Section: Resultsmentioning
confidence: 80%
“…All other solvents and chemicals were obtained from RCI Labscan Ltd (Samutsakorn, Thailand), were of either analytical reagent grade or high‐performance liquid chromatography (HPLC) grade, and were used as received unless otherwise stated. Synthetic urine was prepared in deionized water using the following components: urea (1.2 × 10 −2 mol L −1 ), creatinine (1.3 × 10 −2 mol L −1 ), MgCl 2 (2.0 × 10 −3 mol L −1 ), CaCl 2 (2.0 × 10 −3 mol L −1 ), NaH 2 PO 4 .2H 2 O (8.0 × 10 −3 mol L −1 ), NH 4 Cl (8.0 × 10 −3 mol L −1 ), K 2 SO 4 (1.0 × 10 −2 mol L −1 ), and NaCl (1.6 × 10 −2 mol L −1 ). Synthetic urine and healthy human urine samples were diluted 10 times with phosphate‐buffered solution (PBS, pH 7.0) and added the known amount of HSA and used in further studies.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although these methods could complete the analysis accurately, they usually suffer from drawbacks such as insensitivity, narrow linear range and complicated detection procedures, etc. Therefore, the search for a sensitive, reliable, and convenient approach for detecting serum albumin has attracted increasing interests (9)(10)(11)(12)(13). Fluorescent chemosensors, which have been reported to be valid for the detection of serum albumin in the past few years, have attracted increasing interests due to their merits of high sensitivity, fast analysis, non-destructive emission signals and low cost (14)(15)(16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%